2023
DOI: 10.3390/medicina59030582
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience of Robot-Assisted Transabdominal Preperitoneal (TAPP) Inguinal Hernia Repair by a Single Surgeon in South Korea

Abstract: Background and Objectives: Inguinal hernia is a common surgical disease. Traditional open herniorrhaphy has been replaced by laparoscopic herniorrhaphy. Nowadays, many attempts at robotic herniorrhaphy have been reported in western countries, but there have been no reports in South Korea. The purpose of this study is to report our initial experience with robotic inguinal hernia surgery, compared to laparoscopic inguinal hernia surgery. Materials and Methods: We analyzed the clinical data from 100 patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Eight articles [ 12 15 , 17 20 ] were non-randomized controlled studies, and all of them received high-quality ratings based on the Newcastle-Ottawa Scale (NOS). Among these, 2 articles [ 14 , 17 ] scored 8 points, while the remaining 6 articles scored 7 points [ 12 , 13 , 15 , 18 20 ]. The detailed scoring results are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight articles [ 12 15 , 17 20 ] were non-randomized controlled studies, and all of them received high-quality ratings based on the Newcastle-Ottawa Scale (NOS). Among these, 2 articles [ 14 , 17 ] scored 8 points, while the remaining 6 articles scored 7 points [ 12 , 13 , 15 , 18 20 ]. The detailed scoring results are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A random-effects model was used to combine the effect sizes for the meta-analysis, which indicated that the cost in the RTAPP group was higher than that in the LTAPP group [MD = $4.17 thousand, 95% CI (2.59, 5.76), P < 0.00001], and this difference was statistically significant. Sensitivity analysis was conducted, and when the study by Choi 2023 [ 13 ] or Prabhu 2020 [ 21 ] was excluded, the results showed no statistically significant difference in cost between the two groups. Therefore, it suggests that the stability of the results is relatively low, and it is recommended that future researchers conduct more studies on this aspect, as shown in Fig 4 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations